Genome Editing Enhanced Abiotic Stress Tolerance in Cereal Crops - Shambhu Krishan Lal; Gullnaj Khatoon; Anurag Kumar; Krishan Kumar; Rakesh Kumar; Xiaoping Pan; Sudhir Kumar; Vijai Pal Bhadana; Avinash Pandey; Madan Kumar; Khela Ram Soren; Varakumar Panditi (Functional & Integrative Genomics, 2026)

Spatio-temporal dynamics of urban thermal-pollution interactions in Delhi and its surrounding areas: A remote sensing and GAM modelling approach - Shadman Nahid; Prasenjit Acharya; Krishan Kumar; Ram Pravesh Kumar (Environmental Research, 2026)

Bio-preservative strategies for seafood preservation: Technologies, mechanisms, and future perspectives - Pallavi Bhalavey; Sanjeev Sharma; Krishan Kumar Yadav; Khusbu Gurawa; Rishi Pal Yadav; Ritika Tandel; Harsh Pandey; H.U. Shruthi; Isha Kumari; Shrishti Sharma (Food Bioscience, 2026)

Upcycling single-use polyethylene terephthalate plastics waste into oxygen-rich CQDs for enhanced photoelectrocatalytic two-electron ORR: Mechanistic insights into selective H2O2 generation - Surendra Saini; Mukul Sethi; Priyanka Meena; Aditya Gurjar; Krishan Kumar; D.K. Mahawar; Sana Ullah; Dirk Ziegenbalg; Sven Rau; Vijay Parewa (Chemical Engineering Journal, 2026)

Development of an efficient and reproducible multiple shoot regeneration system in contrasting blast-tolerant indica rice - Anurag Kumar; Ragul Ramasamy; Vijay Sheri; Gullnaj Khatoon; Prahlad Potam; Sudhir Kumar; Uzma Afreen; Acharya Arpita; Sandip Garai; Busa Abhishek Kumar; Shambhu Krishan Lal (Vegetos, 2026)

Advanced glycation end products and PTSD: molecular insights and dietary approaches for neuropsychiatric health - Km Deeksha; Krishan Kumar Verma; Anjali Saini (Metabolic Brain Disease, 2026)

Assessment of Carbon and Phosphorus Stoichiometry in Different Land use Systems as a Tool for Future Planning in Agroecosystems in North Central India - Ram Swaroop Meena; Kundan Kumar Singh; Gourisankar Pradhan; Suchismita Satapathy; Sanjeev Kumar; Krishan Kant Mina; Sandeep Kumar; Cherukumalli Srinivasa Rao; Rattan Lal (Anthropocene Science, 2026)

Integration of mass spectrometry and molecular biotechnology to study bioaerosols - Krishan Kumar; Priyanka Dutta (Chemosphere, 2026)

Investigating the Dharali disaster in Uttarakhand, India on August 5, 2025: perspectives from multiple Earth observation datasets - Arnab Chowdhury; Sahil Kundal; Indrakant Behera; Krishan Kumar; Pavan Sharma; Alok Bhardwaj (Landslides, 2026)

Canopy orientation influences sunburn fruit temperature and peel anatomy in Kinnow and Daisy mandarins - Subhash Chander; Khushdeep Singh; Krishan Kumar (Vegetos, 2026)

Role of n-alkanes in identifying biogenic and anthropogenic sources of ambient aerosols - Krishan Kumar (Science of The Total Environment, 2026)

Sustainable pathways for post-life lithium-ion batteries: Evaluation, recycling, and reuse toward a circular economy - Banshidhar; Shweta Bhatt; Sunil Kumar Srivastava; Yedluri Anil Kumar; Upendra Kumar; R.N. Rai; Dimple Kumari; Krishan Prasad Sharma; Laxman Singh (Next Research, 2026)

Advances in tools, strategies, and applications of mining of microbial genomes for novel antimicrobials: a comprehensive review - Bhanu Krishan; Anu Kumar; Wamik Azmi (Folia Microbiologica, 2026)

Assessment of Groundwater and Surface Waterlogging in the Indira Gandhi Nahar Project (IGNP) Phase-I, India, Using Google Earth Engine - Survey Daman Sharma; Nitesh Patidar; Manmohan Kumar Goel; Anupma Sharma; Gopal Krishan; Surjeet Singh; Sumant Kumar (Journal of the Indian Society of Remote Sensing, 2026)

Biological activities of citrus fruit-derived copper oxide nanoparticles: towards sustainable antimicrobial and antioxidant solutions - Bhanu Krishan; Anu Kumar; Wamik Azmi; Sunny Dhiman (Folia Microbiologica, 2026)

Mitochondrial Perspective on Species Complexes and Evolutionary Dynamics Within Genus Channa - Sonakshi Modeel; Meenu Chaurasia; Sneha Siwach; Padma Dolkar; Rakesh Kumar Negi; Ram Krishan Negi (Biochemical Genetics, 2026)

Effects of Planting Geometry on the Growth, Yield and Quality of the Bael (Aegle Marmelos Correa) Variety ‘Narendra Bael-5’ Under a Semi-arid Region of Haryana - Anuradha Bishnoi; Mukesh Kumar; Krishan Kant Meena; Manoj Kumar Buswal; Balbir Singh; Punam Saini; Pooja (Applied Fruit Science, 2026)

Response of Strawberry (Fragaria × ananassa Duch.) to Plant Density and Column Size in a Vertical Soilless Cultivation System - Vikas Kumar Sharma; A. K. Godara; Deepak Kaushik; Krishan Kant Meena; Sushil Sharma; Adesh Kumar; Arvind Malik; Prince (Applied Fruit Science, 2026)

Carbon dioxide sequestration, bioremediation, and production of value-added products from freshwater filamentous green algae - Riya Singh; Riya Sharma; Krishan Pal; Rama Kant; Elizabeth A. Bergey; Dhananjay Kumar; Lalit Kumar Pandey (Systems Microbiology and Biomanufacturing, 2026)

Growth, production and biochemical attributes of fenugreek (Trigonella foenum-graecum L.) genotypes in Chhattisgarh, India - Krishan Pal Singh; Beena Singh; Abhishek Raj; Arnab Banerjee; Manoj Kumar Jhariya; Khemraj Sahu; S. L. Sawargaonkar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2026)

Kaolin and salicylic acid mitigate sunburn and enhance stress-responsive biochemical and fruit quality traits in Daisy Mandarin (Citrus reticulata Blanco) under arid conditions - Khushdeep Singh; Subhash Chander; Shalini Jhanji; Krishan Kumar; Gurteg Singh (Journal of Plant Biochemistry and Biotechnology, 2026)

Emulsion-based strategies to enhance the physicochemical and structural properties of fish surimi: A comprehensive review - Sanjeev Sharma; Krishan Kumar Yadav; Soibam Ngasotter; Rachna Gulati; Pallavi Bhalavey; Rishi Pal Yadav; Khushbu Gurawa; Deeksha Hooda; Nirmal Patel; Sourabh Majoka (Food Research International, 2026)

Effect of Heading-Back Height on the Rejuvenation of a Senile Ber Orchard (Ziziphus mauritiana Lamk.) Cv. ‘Gola’ - Anuradha Bishnoi; Mukesh Kumar; Krishan Kant Meena; Sudha Bishnoi (Applied Fruit Science, 2026)

Traditional Grewia optiva based agroforestry systems in the northwestern himalayas: a comprehensive study of carbon, soil health, and nutritional value - Ashok Kumar; Rohit Bishist; D. R. Bhardwaj; Rajesh Kaushal; Prem Prakash; Rishav Sharma; Krishan Lal Gautam; Sakshi Tomar (Agroforestry Systems, 2026)

Ce3+-Doped Mg-Zn Ferrite/CNTs Hybrid Nanocomposites for Efficient Sunlight-Driven Dye Degradation - Parveen Kumari; Krishan Kumar (Water, Air, & Soil Pollution, 2025)

Low-Cost Adsorbents: A Sustainable Strategy for Emerging Contaminant Mitigation - Deepak Kumar; Jyoti Rani; Krishan Kumar Selwal (Water, Air, & Soil Pollution, 2025)

Investigation of physical causes for long-term deformation at urbanized towns in Indian himalayas: a case study for Joshimath, Uttarakhand - Krishan Kumar; Arnab Chowdhury; Alok Bhardwaj (Natural Hazards, 2025)

A comprehensive overview of cyanogenic glycosides: Toxicology and innovative sensing approaches - Arindam Niyogi; Soumyadeb Bhattacharyya; Souvik Pal; Subhankar Mukherjee; Subrata Sarkar; Koustuv Ghosh; Alokesh Ghosh; Kumaraswamy Jeyaram; Santosh Keisam; Sirshendu Chatterjee; Om Krishan Singh; Samit Kumar Ray (Food Control, 2025)

Zinc Homeostasis and Biofortification in Crop Plants: Towards Efficient Zinc Utilization - Madan Kumar; Ekta Narwal; Sujay Rakshit; Sujit Kumar Bishi; Vijai Pal Bhadana; Mahesh Kumar; Shambhu Krishan Lal; Monika; Uday Chand Jha; Suman Roy; Jayanta Layek (Journal of Plant Growth Regulation, 2025)

QTransLeafNet: A Quantum-Enhanced and Explainable Deep Learning Framework for Segmentation and Classification of Apple Leaf Diseases - Krishan Kumar; Shiva Mehta; Alka Singh; Tejinder Pal Singh Brar; Harpal Singh; Vinay Kukreja (Applied Fruit Science, 2025)

Altitude-driven changes in carbon storage, soil properties, and leaf nutritional value of Quercus semecarpifolia in the northwestern Himalayas - Rishav Sharma; Rohit Bishist; Rajesh Kaushal; Prem Prakash; Krishan Lal Gautam; Ashok Kumar; Harish Sharma; Varun Thakur; Munesh Kumar (Environmental Sustainability, 2025)

Application of Diagnosis and Recommendation Integrated System (DRIS) to Sugarcane: A Systematic Literature Review - Amanda Magalhães Bueno; Rilner Alves Flores; Wilson Mozena Leandro; Aline Franciel de Andrade; Glenio Guimarães Santos; Krishan Kumar Verma (Journal of Soil Science and Plant Nutrition, 2025)

Extraction optimization of bioactive compounds from Vitex negundo through RSM: GC–MS, FTIR, in silico analysis, and antibacterial activity - Eti Sharma; Nisha Gaur; Sandeep Singh; Kartavya Mathur; Krishan Kumar; Nitin Wahi; Gunjan Garg (Journal of Plant Biochemistry and Biotechnology, 2025)

An Assessment of Atmospheric Convection Trends Over India Using Radiosonde Derived CAPE and Other Proxies - Piyush Kumar Ojha; Amit Kumar Mishra; Vinay Singh; Saloni Sharma; Aniket Gupta; Amit Prakash; Omvir Singh; Krishan Kumar (International Journal of Climatology, 2025)
Convective Available Potential Energy (CAPE) is widely considered a good measure of atmospheric convection. Though there is a general consensus among the scientific community about the increasing trend of atmospheric convection in a warming scenario, the tropical region presents an uncertain picture of atmospheric convection as recent studies report disagreement between radiosonde and ERA5‐derived CAPE trends. In this study, we attempt to address this uncertainty over the Indian region by considering several other proxies of atmospheric convection, namely surface equivalent potential temperature, outgoing longwave radiation, upper tropospheric carbon monoxide, convective precipitation and lightning in addition to the CAPE trends obtained from radiosonde based observations and ERA5 model‐based data sets for the period 2001 to 2024. Our results of radiosonde‐reported CAPE from 29 stations spread across the entire India show a significant decreasing trend at 0Z (−30.85 J/kg/year), whereas a slightly increasing trend (0.5 J/kg/year) is observed over these stations in ERA5 CAPE data sets at 0Z. Further, our analysis reveals that the CAPE trend based on radiosonde observations over India is reversed if we compute CAPE following the surface‐based approach (i.e., SBCAPE). The disagreement between radiosonde and ERA5 CAPE trends raises questions about the reliability of radiosonde‐reported CAPE as a measure of atmospheric convection over India. However, results from all other proxies suggest an increasing trend of atmospheric convection over India. Therefore, we conclude that inferences based solely on radiosonde‐reported CAPE may not be sufficient to assess the trends of atmospheric convection over India, and a more holistic approach based on several proxies is needed.

Rhizofiltration of Caesium and Strontium Through the Use of Aquatic Plants Eichhornea crassipes (Mart.) Solms and Monochoria hastata (L.) Solms-Laub - Brundaban Sarojini Manisha Singh; Nabin Kumar Dhal; Manish Kumar; Dinakrushna Mohapatra; Hariharan Seshadri; Krishan Kumar; Dharitri Mishra (International Journal of Environmental Research, 2025)

Artificial Intelligent and Internet of Things framework for sustainable hazardous waste management in hospitals - Amit Krishan Kumar; Yasir Ali; Rahul R. Kumar; Mansour H. Assaf; Sadia Ilyas (Waste Management, 2025)

Analysis of the Degradation Products of the Organic Materials Present in the c-Si PV Modules, Emitted during a Pyrolysis Treatment and Recycling Strategy for Circular and Sustainable Development - Krishan Kumar Patel; Sudhanshu Mallick (Circular Economy and Sustainability, 2025)

Soil Water Balance and Productivity of Different Maize-Based Crop Sequences Compared to Rice–Wheat System under Contrasting Irrigation Regimes in North–West India - Navneet Kaur; Krishan Kumar Vashist; A. S. Brar (Agricultural Research, 2025)

Emerging technologies for assessing the occurrence, fate, effects, and remediation of plastics in the environment - Krishan Kumar; Annu Khatri; Indu Shekhar Thakur (Environmental Monitoring and Assessment, 2025)

Hepatic encephalopathy in cirrhosis: therapies and developments - Ajay Kumar Mishra; Radha Krishan Dhiman (Metabolic Brain Disease, 2025)

Energy budgeting and economic analysis of coriander crop production in central India - Sushma Painkra; Krishan Pal Singh; Beena Singh; Manoj Kumar Jhariya; Arnab Banerjee; Khemraj Sahu; Purnima Haldar; Bhagwat Kumar (Environment, Development and Sustainability, 2025)

Microbiome of caves for bioprospecting: a critical review - Annu Khatri; Krishan Kumar; Indu Shekhar Thakur (Systems Microbiology and Biomanufacturing, 2025)

Environmental DNA (eDNA): an eco-friendly approach for conservation of Indian freshwater diversity—a review - Ashish Sahu; Mahender Singh; Rishikesh Krishan Laxmi; Tarang Kumar Shah; Madhu Sharma (Environmental Science and Pollution Research, 2025)

Unlocking the potential of fishery waste: exploring diverse applications of fish protein hydrolysates in food and nonfood sectors - Anand Vaishnav; Jham Lal; Naresh Kumar Mehta; Saswat Mohanty; Krishan Kumar Yadav; Mocherla Bhargavi Priyadarshini; Payel Debbarma; Nongthongbam Sureshchandra Singh; Bikash Kumar Pati; Soibam Khogen Singh (Environmental Science and Pollution Research, 2025)

Long-term effect of Bt cottonseed cake on nutrient utilisation, growth performance and health of rams in tropical conditions - Krishan Kunwar Singh; Pushpendra Koli; Sultan Singh; Vijay Kumar Yadav; Asim Kumar Misra; Subhendu Bikas Maity; P. Govindraj; R. Karuppiyan (Tropical Animal Health and Production, 2025)

Emerging technologies for occurrence, fate, effect and remediation of organic contaminants in soil and sludge - Annu khatri; Krishan kumar; Indu Shekhar Thakur (Systems Microbiology and Biomanufacturing, 2025)

Identification of Phytophthora nicotianae tolerant citrus hybrids using subordinate function analysis of disease and morpho-physio-biochemical responses - Harsimran Singh; Krishan Kumar; Neeraj Kumar; Rimaljeet Kaur; Anita Arora; Nirmaljit Kaur; Jaswinder Brar; Harleen Kaur (Rhizosphere, 2024)

Satellite derived air pollution climatology over India and its neighboring regions: Spatio-temporal trends and insights - Sneha Dhankar; Amit Kumar Mishra; Krishan Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Conjoint Application of Nutrients as Customized Fertilizers Influences Growth and Yield Characteristics of Brassica juncea L., Augmented Profitability and Nutrient Use Efficiency Indices - Vasudev Meena; Mohan Lal Dotaniya; Murli Dhar Meena; Ram Swaroop Jat; Mukesh Kumar Meena; Ram Lal Choudhary; Hari Singh Meena; Bheeru Lal Meena; Lalit Krishan Meena; Pramod Kumar Rai (Journal of Soil Science and Plant Nutrition, 2024)

Implications of urbanization on the seasonal dynamics and long-term trends in the thermal climate of a city in the Himalayan foothills of India - Gayatri Singh; Piyush Kumar Ojha; Shivam Kumar Sharma; Priyanka Kumari; Alok Kumar Pandey; Amit Kumar Mishra; Krishan Kumar (Journal of Geovisualization and Spatial Analysis, 2024)

Green synthesis of N-doped-carbon dots/ZnO for enhanced photocatalytic degradation of methylene blue dye: optimization of reaction parameters - Neeru Rani; Sandeep Kumar; Krishan Kumar (Environmental Science and Pollution Research, 2024)

Exposure to traffic and greenspace, and associations with respiratory health in urban India - Sowmya Malamardi; Katrina Lambert; Sheetu Singh; Sundeep Salvi; Sushil K. Kabra; Meenu Singh; Shally Awasthi; Arvind Kumar Sharma; Sabir Mohammed; Thevaruparambil U. Sukumaran; Aloke G. Ghoshal; Nishtha Singh; et al. (Urban Climate, 2024)

Double Dormancy in a Threatened Western Himalayan Population of Polygonatum cirrhifolium (Maha-Meda): Response to Ambient Storage and Pre-treatments - Ram Krishan; Rajender Kumar Sharma; Vijay Kumar; Shanti S. Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Observational evidence of changing cloud macro-physical properties under warming climate over the Indian summer monsoon region - Saloni Sharma; Piyush Kumar Ojha; Vaibhav Bangar; Chandan Sarangi; Ilan Koren; Krishan Kumar; Amit Kumar Mishra (Science of The Total Environment, 2024)

Multi-omics and advance technologies in biodegradation of emerging contaminants and eco-estrogens in environmental waste - Manan Kaur Ghai; Annu Khatri; Krishan Kumar; Indu Shekar Thakur (Total Environment Advances, 2024)

Oxidative stress dynamics revealed the role of H2O2 in citrus rootstocks sensitivity to Phytophthora nicotianae - Neeraj Kumar; Harsimran Singh; Krishan Kumar; Rimaljeet Kaur; Anita Arora; Nirmaljit Kaur (Physiological and Molecular Plant Pathology, 2024)

Fabrication of magnetite/GO/potassium copper hexacyanoferrate nanocomposite for removal of radioactive cesium ions - Isha Riyal; Krishan Kant Singh; Archana Ramola; Jyoti Rawat; Sanjay Kumar Pathak; Surajit Panja; Himani Sharma; Charu Dwivedi (Journal of Environmental Radioactivity, 2024)

Recent Advancements in Nitrogen Use Efficiency in Crop Plants Achieved by Genomics and Targeted Genetic Engineering Approaches - Shambhu Krishan Lal; Payal Gaggar; Sudhir Kumar; Mallana Gowdra Mallikarjuna; Chandrapal Vishwakarma; Sujay Rakshit; Avinash Pandey; V. Mohan Murali Achary; Sahil Mehta (Plant Molecular Biology Reporter, 2024)

Pyrolysis Gas Analysis of Ethylene-vinyl Acetate (EVA) and Poly-vinylidene Fluoride (PVDF) Polymers Encapsulated in c-Si Photovoltaic Solar Module to Facilitate Recycling - Krishan Kumar Patel; Sudhanshu Mallick (Circular Economy and Sustainability, 2024)

Microbial Consortia: Promising Tool as Plant Bioinoculants for Agricultural Sustainability - Rajeshwari Negi; Babita Sharma; Tawseefa Jan; Tanvir Kaur; Sohini Chowdhury; Monit Kapoor; Sangram Singh; Anu Kumar; Ashutosh Kumar Rai; Sarvesh Rustagi; Sheikh Shreaz; Divjot Kour; et al. (Current Microbiology, 2024)

Evaluation of Gemcitabine and Epigallocatechin-3-Gallate Loaded Solid Lipid Nanoparticles on Benzopyrene Induced Lung Cancer Model Via Intranasal Route: Improved Pharmacokinetics and Safety Profile - Mohini Mishra; Rinki Verma; Aditya Sharma; Krishan Kumar; Ruchi Chawla (AAPS PharmSciTech, 2024)

Agriculture models for restoring degraded land to enhance CO2 biosequestration and carbon credits in the Vindhyan region of India - Ram Swaroop Meena; Gourisankar Pradhan; Kanchan Singh; Sandeep Kumar; Ambuj Kumar Singh; K.S. Shashidhar; Krishan Kant Mina; Ch. Srinivasa Rao (Science of The Total Environment, 2024)

Nexus between fintech, green finance and natural resources management: Transition of BRICS nation industries from resource curse to resource blessed sustainable economies - Sanjeev Yadav; Ashutosh Samadhiya; Anil Kumar; Sunil Luthra; Krishan Kumar Pandey (Resources Policy, 2024)

Cross-transferability of Rubus ellipticus EST–SSR markers for genetic diversity analysis of peach (Prunus persica) - Samriti Sharma; Rajinder Kaur; Krishan Kumar; Heerendra Sagar (Genetic Resources and Crop Evolution, 2024)

Evaluation of morphology and yield of turmeric (Curcuma longa L.) genotypes under agroclimatic conditions of Chhattisgarh plains, India - Krishan Pal Singh; Beena Singh; Abhishek Raj; Manoj Kumar Jhariya; Arnab Banerjee; S. L. Sawargaonkar (Vegetos, 2024)

VOC source apportionment, reactivity, secondary transformations, and their prioritization using fuzzy-AHP method in a coal-mining city in India - Nidhi Malik; Vivek Singh; Krishan Kumar; Suresh Pandian Elumalai (Environmental Science and Pollution Research, 2024)

Review on interactions between nanomaterials and phytohormones: Novel perspectives and opportunities for mitigating environmental challenges - Dharmendra Kumar; Ritu Singh; Sudhir K. Upadhyay; Krishan K. Verma; Ravi Mani Tripathi; Haitao Liu; Om Parkash Dhankher; Rudra Deo Tripathi; Shivendra V. Sahi; Chandra Shekhar Seth (Plant Science, 2024)

Shoreline Change Detection and Future Prediction of Sundarban Delta Using Remote Sensing Data and Digital Shoreline Analysis System - Krishan Kundu; Jyotsna Kumar Mandal (Journal of the Indian Society of Remote Sensing, 2024)

Nanotechnology, a frontier in agricultural science, a novel approach in abiotic stress management and convergence with new age medicine-A review - Safoora Mariyam; Sudhir K. Upadhyay; Koushik Chakraborty; Krishan K. Verma; Joginder Singh Duhan; Sowbiya Muneer; Mukesh Meena; Rajesh Kumar Sharma; Gajanan Ghodake; Chandra Shekhar Seth (Science of The Total Environment, 2024)

Deciphering mucin degrading ability and safety aspects of enterococcus strain from human feces - Garima Deswal; Harsha Nirvan; Manjit K. Selwal; Krishan Kumar Selwal (Biologia, 2024)

Geophysical signatures of the Saraswati River palaeochannel in a part of Kurukshetra district, Haryana, India - Sushil Kumar; Ashish Jangra; Nepal Chandra Mondal; Bhagwan Singh Chaudhary; Krishan Kumar; Aakash Deep; Kamal; Savita Singh (Journal of Earth System Science, 2024)

Carbon dots as potential candidate for photocatalytic treatment of dye wastewater - Tripti Tripti; Permender Singh; Neeru Rani; Sandeep Kumar; Krishan Kumar; Parmod Kumar (Environmental Science and Pollution Research, 2023)

In Vivo Cancer Microenvironment Responsive Glycan Receptor-Targeted Nanoparticles for Gemcitabine Delivery to Benzo[a]pyrene-Induced Lung Cancer Model - Krishan Kumar; Rinki Verma; Manjit; Priya; Mohini Mishra; Varsha Rani; Ruchi Chawla (AAPS PharmSciTech, 2023)

First report on Bacillus subtilis EU-WG-01 endophytic bacterium from wheat grass and development of probiotic formulation - Tawseefa Jan; Rajeshwari Negi; Babita Sharma; Divjot Kour; Sanjeev Kumar; Imran Sheikh; Praneet Chauhan; Krishan Kumar; Naseer Ahmed; Ajar Nath Yadav (Food Bioscience, 2023)

Soil microbes: a natural solution for mitigating the impact of climate change - Aradhna Kumari; Munmun Dash; Santosh Kumar Singh; M. Jagadesh; Bhupendra Mathpal; P. K. Mishra; Sunil Kumar Pandey; Krishan K. Verma (Environmental Monitoring and Assessment, 2023)

Soil properties and carbon dynamics under coffee-based agroforestry system in Bastar region of Chhattisgarh, India - Krishan Pal Singh; Beena Singh; Manoj Kumar Jhariya; Khemraj; Abhishek Raj; Arnab Banerjee; D. S. Thakur (Environment, Development and Sustainability, 2023)

Microplastics and biobased polymers to combat plastics waste - Krishan Kumar; Reddicherla Umapathi; Seyed Majid Ghoreishian; Jitendra N. Tiwari; Seung Kyu Hwang; Yun Suk Huh; Pannuru Venkatesu; Nagaraj P. Shetti; Tejraj M. Aminabhavi (Chemosphere, 2023)

Studies on natural regeneration, floristic composition, biomass, carbon density and soil properties along an altitudinal gradient in the north-western Himalayas, India - Ghanshyam Singh; Vimal Chauhan; C.L. Thakur; M.L. Verma; Rohit Bishist; Prem Prakash; Krishan Lal Gautam; Harish Sharma; Rushal Dogra; Kamal Kishore; Munesh Kumar (Forest Ecology and Management, 2023)

Corrigendum to “Gold nanoclusters supported Molybdenum diselenide-porous carbon composite as an efficient electrocatalyst for selective ultrafast probing of chlorpyrifos-pesticide” [Chem. Eng. J. 472(2023) 145048] - A.T. Ezhil Vilian; Ali Mohammadi; Soobin Han; Jitendra N. Tiwari; Krishan Kumar; Annamalai Senthil Kumar; Adhimoorthy Saravanan; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

A Web-Enabled Tool for Site Suitability Mapping for Managed Aquifer Recharge (MAR) Using Google Earth Engine (GEE) and Multi-Criteria Decision Analysis (MCDA) - Nitesh Patidar; Basant Yadav; Sumit Kumar; Abhay Raj; Gopal Krishan; Surjeet Singh; Bhaskar Jyoti Deka; Sanghyun Jeong; Ashish Pandey; Yutaka Matsuno; R. D. Singh (Water Resources Management, 2023)

Aflatoxin M1 decreases the expression of genes encoding tight junction proteins and influences the intestinal epithelial integrity - Lal Krishan Kumar; Surya Kant Verma; Rajeev Chandel; Meet Thumar; Dheer Singh; Suneel Kumar Onteru (Mycotoxin Research, 2023)

Fluoride contamination in ground-drinking water and urine from rural population of Uttar Pradesh, India - Krishan K. Verma; Abhishek Kumar; Munna Singh; Chhedi Lal Verma (Journal of Geochemical Exploration, 2023)

Recent advancement in nanomaterials for the detection and removal of uranium: A review - Neeru Rani; Permender Singh; Sandeep Kumar; Parmod Kumar; Vinita Bhankar; Nisha Kamra; Krishan Kumar (Environmental Research, 2023)

Diversity, distribution and role of probiotics for human health: Current research and future challenges - Tawseefa Jan; Rajeshwari Negi; Babita Sharma; Divjot Kour; Sanjeev Kumar; Ashutosh Kumar Rai; Sarvesh Rustagi; Sangram Singh; Mohd Aaqib Sheikh; Krishan Kumar; Naseer Ahmed; Ajar Nath Yadav (Biocatalysis and Agricultural Biotechnology, 2023)

Concurrent Overexpression of Rice GS1;1 and GS2 Genes to Enhance the Nitrogen Use Efficiency (NUE) in Transgenic Rice - Shambhu Krishan Lal; Sahil Mehta; Dhandapani Raju; V. Mohan Murali Achary; Ajay Kumar Venkatapuram; Shashank Kumar Yadav; Hemangini Parmar; Rakesh Pandey; Varakumar Panditi; Vijay Sheri; Anil Kumar Singh; Viswanathan Chinnusamy; et al. (Journal of Plant Growth Regulation, 2023)

Biomass, carbon stock, CO2 mitigation and carbon credits of coffee-based multitier cropping model in Central India - Krishan Pal Singh; Beena Singh; Sanjay Kumar Patil; Chhatra Pal Rahangdale; Arnab Banerjee; Rajshree Shukla; Khemraj Sahu; Manoj Kumar Jhariya (Environmental Monitoring and Assessment, 2023)

Health risk assessment from exposure to ambient VOCs and particulate matter in different functional zones in Dhanbad, India - Nidhi Malik; Suresh Pandian Elumalai; Krishan Kumar (Science of The Total Environment, 2023)

Simultaneous monitoring and dietary risk assessment of 386 pesticides in market samples of black tea - Vandana Tripathy; Krishan Kumar Sharma; Ruchi Gupta; Rajbir Yadav; Suneeta Devi; Khushbu Sharma; Gitansh Singh; Shobhita Kalra; Akanksha Aggarwal; Kesar Tandekar; Ankita Verma; Suresh Walia (Food Chemistry, 2023)

Gold nanoclusters supported Molybdenum diselenide-porous carbon composite as an efficient electrocatalyst for selective ultrafast probing of chlorpyrifos-pesticide - A.T. Ezhil Vilian; Ali Mohammadi; Soobin Han; Jitendra N. Tiwari; Krishan Kumar; Annamalai Senthil Kumar; Adhimoorthy Saravanan; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

pH-influenced self-assembled stealth nanoscaffolds encapsulating memantine for treatment of Alzheimer’s disease - Varsha Rani; Rinki Verma; Krishan Kumar; Ruchi Chawla (Journal of Biosciences, 2023)

Assessing the biomass-based carbon dots and their composites for photocatalytic treatment of wastewater - Permender Singh; Neeru Rani; Sandeep Kumar; Parmod Kumar; Brij Mohan; Pallavi; Vinita Bhankar; Navish Kataria; Ravi Kumar; Krishan Kumar (Journal of Cleaner Production, 2023)

Dopant-driven recombination delay and ROS enhancement in nanoporous Cd1-xCuxS heterogeneous photocatalyst for the degradation of DR-23 dye under visible light irradiation - Savita Meena; Mukul Sethi; Swati Meena; Pratibha Saini; Krishan Kumar; Surendra Saini; Sumita Shekhawat; Mohan Lal Meena; Anshu Dandia; Shawn D. Lin; Vijay Parewa (Environmental Research, 2023)

Therapeutic targeting of the tumor microenvironments with cannabinoids and their analogs: Update on clinical trials - Aliya Sheik; Marzieh Ramezani Farani; Eunsu Kim; Suheon Kim; Vivek Kumar Gupta; Krishan Kumar; Yun Suk Huh (Environmental Research, 2023)

Palladium nanoparticles anchored MoS2-MXene composite modified electrode for rapid sensing of toxic bisphenol A in aqueous media - A.T. Ezhil Vilian; Jitendra N. Tiwari; Munirah Alhammadi; Gokul Bhaskaran; Seung-Kyu Hwang; Suheon Kim; Krishan Kumar; Annamalai Senthil Kumar; Yun Suk Huh; Young-Kyu Han (Chemical Engineering Journal, 2023)

Corrigendum to “Nickel ions modified Co-Mg nanophotocatalysts for solar light-driven degradation of antimicrobial pharmaceutical effluents” [J. Water Process Eng., June 2022, 47, 102785] - Rohit Jasrotia; Ankit Verma; Ritesh Verma; Sachin Kumar; Jahangeer Ahmed; Bal Krishan; Swati Kumari; Asiya M. Tamboli; Swati Sharma; Susheel Kalia (Journal of Water Process Engineering, 2023)

An evaluation of the three-component pubic symphyseal human age estimation method: a CT-based exploration in an Indian population - Varsha Warrier; Rutwik Shedge; Pawan Kumar Garg; Shilpi Gupta Dixit; Kewal Krishan; Tanuj Kanchan (The Science of Nature, 2023)

Foliar Application of Potassium Salt of Active Phosphorus (PSAP) Mitigates Insect Pests and Improves Yield Along With Sugarcane Quality in Response to Agroclimatic Conditions of Punjab - Rajan Bhatt; Krishan K. Verma; Rajinder Kumar; Gulzar S. Sanghera (Sugar Tech, 2023)

RNA Sequencing of Intraoperative Peritumoral Tissues Reveals Potential Pathways Involved in Glioma-Related Seizures - Krishan Kumar; Vivek Dubey; Syeda S. Zaidi; Manjari Tripathi; Fouzia Siraj; Mehar Chand Sharma; P. Sarat Chandra; Ramesh Doddamani; Aparna Banerjee Dixit; Jyotirmoy Banerjee (Journal of Molecular Neuroscience, 2023)

Estimation of biomass and carbon storage potential in agroforestry systems of north western Himalayas, India - Harish Sharma; K.S. Pant; Rohit Bishist; Krishan Lal Gautam; Ludarmani; Rushal Dogra; Munesh Kumar; Amit Kumar (CATENA, 2023)

Revisiting the therapeutic potential of gingerols against different pharmacological activities - Samridhi Sharma; Monu Kumar Shukla; Krishan Chander Sharma; Tirath; Lokender Kumar; Jasha Momo H. Anal; Santosh Kumar Upadhyay; Sanjib Bhattacharyya; Deepak Kumar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Ordering the right quantity? Examining the impact of plate size vagueness on food waste in an online food delivery system - Vibha Trivedi; Ashish Trivedi; Krishan Kumar Pandey; Sushil S. Chaurasia (Journal of Cleaner Production, 2023)

Integrated approach for the investigation of groundwater quality through hydrochemistry and water quality index (WQI) - Gopal Krishan; Mohit Kumar; M. Someshwar Rao; Rahul Garg; Brijesh Kumar Yadav; M.L. Kansal; Surjeet Singh; A. Bradley; Marian Muste; L.M. Sharma (Urban Climate, 2023)

Assessment of groundwater salinity using principal component analysis (PCA): a case study from Mewat (Nuh), Haryana, India - G. Krishan; A. Bhagwat; P. Sejwal; B. K. Yadav; M. L. Kansal; A. Bradley; S. Singh; M. Kumar; L. M. Sharma; M. Muste (Environmental Monitoring and Assessment, 2023)

Assessment of seed biology of the Himalayan medicinal herb Phytolacca acinosa Roxb., the Indian pokeweed, from the perspective of longevity, conservation and propagation - Ram Krishan; Rajender Kumar Sharma; Shanti S. Sharma (The Nucleus, 2022)

Narrowing down molecular targets for improving phosphorus-use efficiency in maize (Zea mays L.) - Krishan Kumar; Pranjal Yadava; Mamta Gupta; Mukesh Choudhary; Abhishek Kumar Jha; Shabir Hussain Wani; Zahoor Ahmed Dar; Bhupender Kumar; Sujay Rakshit (Molecular Biology Reports, 2022)

Seed longevity and storage dependent changes in seed germination aspects of Berberis aristata and B. lycium from Western Himalaya: implications for seed storage and conservation - Ram Krishan; Rajender Kumar Sharma; Vijay Kumar; Mahesh Kumar; Shanti S. Sharma (Vegetos, 2022)

Evaluation of water quality using water quality index, synthetic pollution index, and GIS technique: a case study of the river Gomti, Lucknow, India - Amit Krishan; Anwar Khursheed; Rajeev Kumar Mishra (Environmental Science and Pollution Research, 2022)

Transcriptomic profiling of nonneoplastic cortical tissues reveals epileptogenic mechanisms in dysembryoplastic neuroepithelial tumors - Krishan Kumar; Aparna Banerjee Dixit; Manjari Tripathi; Vivek Dubey; Fouzia Siraj; Mehar Chand Sharma; Sanjeev Lalwani; P Sarat Chandra; Jyotirmoy Banerjee (Functional & Integrative Genomics, 2022)

Nanomaterials photocatalytic activities for waste water treatment: a review - Permender Singh; Brij Mohan; Vasundhara Madaan; Rohit Ranga; Parveen Kumari; Sandeep Kumar; Vinita Bhankar; Parmod Kumar; Krishan Kumar (Environmental Science and Pollution Research, 2022)

Functional characterization of differentially-expressed increased glyphosate resistance (igrA) gene in transgenic rice (Oryza sativa L.) - Varakumar Panditi; Dhirendra Fartyal; Vijay Sheri; Aakrati Agarwal; Sahil Mehta; Shambhu Krishan Lal; Ajay Kumar Venkatapuram; Hemangini Parmar; Sangeetha Karippadakam; Afreen Rashid; Malireddy K. Reddy; V. Mohan Murali Achary (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

How do the sympatric forest mongooses coexist in the Western Ghats landscape? Insights from spatio-temporal approach - Thekke Thumbath Shameer; Sulekha Jameela Backer; Subramani Nandhini; Sreehari Raman; Azim Nisar Mujawar; Jayakumar Yogesh; Krishan Kumar Kaushal; Srinivas Ramachandra Reddy; Anwar Nazia; Raveendranathanpillai Sanil (Community Ecology, 2022)

Persistence evaluation of fluopyram + tebuconazole residues on mango and pomegranate and their risk assessment - Vandana Tripathy; Krishan Kumar Sharma; Soudamini Mohapatra; Lekha Siddamallaiah; Nagapooja Yogendraiah Matadha; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Bhaidas Deore; Cherukuri Sreenivasa Rao; Kaushik D. Parmar; Nitesh S. Litoriya; Paresh G. Shah; et al. (Environmental Science and Pollution Research, 2022)

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Fine-tuning the transcriptional regulatory model of adaptation response to phosphate stress in maize (Zea mays L.) - Pranjal Yadava; Vikram Dayaman; Astha Agarwal; Krishan Kumar; Ishwar Singh; Rachana Verma; Tanushri Kaul (Physiology and Molecular Biology of Plants, 2022)

Development of an efficient and reproducible in vitro regeneration and transformation protocol for tropical maize (Zea mays L.) using mature seed-derived nodal explants - Krishan Kumar; Abhishek Kumar Jha; Bhupender Kumar; Chikkappa G. Karjagi; Alok Abhishek; Geetika Gambhir; Chetana Aggarwal; Akshita Tyagi; Pooja Sharma; Pankaj Pandey; Sujay Rakshit (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Anti-larval activity of actinobacterial extract for Helicoverpa armigera and Spodoptera litura - Kiran Gandhi Bapatla; Krishan Kumar; Lalit Kumar; Bansa Singh; N. P. Singh (International Journal of Tropical Insect Science, 2022)

Impact of ventilation rate and its associated characteristics on greenhouse microclimate and energy use - Mahesh Chand Singh; Krishan Kumar Sharma; Vishnu Prasad (Arabian Journal of Geosciences, 2022)

Trend analysis of temperature, rainfall, and reference evapotranspiration for Ludhiana district of Indian Punjab using non-parametric statistical methods - Mahesh Chand Singh; Sanjay Satpute; Vishnu Prasad; Krishan Kumar Sharma (Arabian Journal of Geosciences, 2022)

A Mini-Review on Potential of Neuropeptides as Future Therapeutics - Deepika Sharma; Krishan Kumar; Gopal Singh Bisht (International Journal of Peptide Research and Therapeutics, 2022)

Horticultural crops tackling stresses: genetic and epigenetic alterations - Samriti Sharma; Arjun Chauhan; Raj Kumar; Sneha Dobhal; Rajinder Kaur; Krishan Kumar; Kamlesh Verma (Genetic Resources and Crop Evolution, 2022)

Mucolytic bacteria: prevalence in various pathological diseases - Krishan Kumar Selwal; Manjit K. Selwal; Zhongtang Yu (World Journal of Microbiology and Biotechnology, 2021)

Source identification and health risk assessment associated with particulate- and gaseous-phase PAHs at residential sites in Delhi, India - Bhupendra P. Singh; Krishan Kumar; Vinod Kumar Jain (Air Quality, Atmosphere & Health, 2021)

Detection and Prediction of Sundarban Reserve Forest using the CA-Markov Chain Model and Remote Sensing Data - Krishan Kundu; Prasun Halder; Jyotsna Kumar Mandal (Earth Science Informatics, 2021)

Study of seasonal variation of PM2.5 concentration associated with meteorological parameters at residential sites in Delhi, India - Bhupendra Pratap Singh; Deepak Singh; Krishan Kumar; Vinod Kumar Jain (Journal of Atmospheric Chemistry, 2021)

Phytohormone signalling and cross-talk to alleviate aluminium toxicity in plants - Alok Ranjan; Ragini Sinha; Shambhu Krishan Lal; Sujit Kumar Bishi; Anil Kumar Singh (Plant Cell Reports, 2021)

Dissipation kinetics and risk assessment of iprovalicarb + propineb fungicide in tomato under different agroclimates - Vandana Tripathy; Krishan Kumar Sharma; Thomas George; Chidanand Shiveshankar Patil; Yogesh Subhash Saindane; Soudamini Mohapatra; Lekha Siddamallaiah; Abdul Rashid Khan Pathan; Amit Kumar Yadav; Khushbu Sharma; Rajbir Yadav; Ruchi Gupta; et al. (Environmental Science and Pollution Research, 2021)

Seasonal Abundance and Source Attribution of Carbonaceous Aerosols at Different Altitude of Mountainous Locations in Uttarakhand Himalaya - Amit Kumar; Sachchidanand Singh; Niraj Kumar; Narendra Singh; Krishan Kumar; Amit K. Mishra; Sapna Chourasiya; H. S. Kushwaha (Aerosol Science and Engineering, 2021)

Genetic variability in Rubus ellipticus collections assessed by morphological traits and EST-SSR markers - Samriti Sharma; Rajinder Kaur; Krishan Kumar; Dinesh Kumar; Amol Kumar U. Solanke (Journal of Plant Biochemistry and Biotechnology, 2021)

Simple Nested Allele-Specific approach with penultimate mismatch for precise species and sex identification of tiger and leopard - George Nittu; Pudupet Madhavan Bhavana; Thekke Thumbath Shameer; Balasundaram Ramakrishnan; Rajan Archana; Krishan Kumar Kaushal; Gulab Dattarao Khedkar; Govindarajan Mohan; Manikkiri Jyothi; Raveendranathanpillai Sanil (Molecular Biology Reports, 2021)

Plant disease detection using computational intelligence and image processing - Vibhor Kumar Vishnoi; Krishan Kumar; Brajesh Kumar (Journal of Plant Diseases and Protection, 2021)

Understanding stable isotope systematics of salinity affected groundwater in Mewat, Haryana, India - Gopal Krishan; N C Ghosh; C P Kumar; Lalit Mohan Sharma; Brijesh Yadav; M L Kansal; Surjeet Singh; S K Verma; Gokul Prasad (Journal of Earth System Science, 2020)

Catalytic peroxidation of acrylic acid from aqueous solution incorporated with highly active La0.5Sr0.5BO3 (B=Cu, Fe and Ni) perovskite-like catalysts - Arvind Kumar; Basheswar Prasad; Krishan Kishor Garg (Journal of Environmental Health Science and Engineering, 2020)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Transfer of grain softness from 5U-5A wheat-Aegilops triuncialis substitution line to bread wheat through induced homeologous pairing - Yogesh Sharma; Imran Sheikh; Ambika Sharma; Ajar Nath Yadav; Krishan Kumar; Parveen Chhuneja; Sewa Ram; Sunil Kumar; Pritesh Vyas; H. S. Dhaliwal (Journal of Plant Biochemistry and Biotechnology, 2020)

Genetically modified crops: current status and future prospects - Krishan Kumar; Geetika Gambhir; Abhishek Dass; Amit Kumar Tripathi; Alla Singh; Abhishek Kumar Jha; Pranjal Yadava; Mukesh Choudhary; Sujay Rakshit (Planta, 2020)

Forest biomass estimation using remote sensing and field inventory: a case study of Tripura, India - Prem Chandra Pandey; Prashant K. Srivastava; Tilok Chetri; Bal Krishan Choudhary; Pavan Kumar (Environmental Monitoring and Assessment, 2019)

Air quality modelling using long short-term memory (LSTM) over NCT-Delhi, India - Mrigank Krishan; Srinidhi Jha; Jew Das; Avantika Singh; Manish Kumar Goyal; Chandrra Sekar (Air Quality, Atmosphere & Health, 2019)

Intermittent normobaric hypoxia facilitates high altitude acclimatization by curtailing hypoxia-induced inflammation and dyslipidemia - Anamika Gangwar; Pooja; Manish Sharma; Krishan Singh; Anita Patyal; Gopinath Bhaumik; Kalpana Bhargava; Niroj Kumar Sethy (Pflügers Archiv - European Journal of Physiology, 2019)

Thermal analysis of solar updraft tower by using different absorbers with convergent chimney - Neeraj Mehla; Krishan Kumar; Manoj Kumar (Environment, Development and Sustainability, 2019)

Exploitation of Walnut (Juglans regia L.) Expressed Sequence Tags for Development of SSR Markers After In Silico Analysis - Sankhyan Shailja; Rajinder Kaur; Chaudhary Shilpa; Krishan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Development of indices for surface and ground water quality assessment and characterization for Indian conditions - Surjeet Singh; N. C. Ghosh; Gopal Krishan; Sumant Kumar; Suman Gurjar; M. K. Sharma (Environmental Monitoring and Assessment, 2019)

Homology Modeling, Molecular Docking and Molecular Dynamics Based Functional Insights into Rice Urease Bound to Urea - Anuj Kumar; Sanjay Kumar; Amit Kumar; Naveen Sharma; Mansi Sharma; Krishan Pal Singh; Madhu Rathore; M. N. V. Prasad Gajula (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Iron oxide labeling does not affect differentiation potential of human bone marrow mesenchymal stem cells exhibited by their differentiation into cardiac and neuronal cells - Sujata Mohanty; Krishan Gopal Jain; Sushmita Bose Nandy; Anupama Kakkar; Manoj Kumar; Amit Kumar Dinda; Harpal Singh; Alok Ray (Molecular and Cellular Biochemistry, 2018)

Evaluation of end use quality and root traits in wheat cultivars associated with 1RS.1BL translocation - Ambika Sharma; Imran Sheikh; Rahul Kumar; Krishan Kumar; Pritesh Vyas; H. S. Dhaliwal (Euphytica, 2018)

Lead: Tiny but Mighty Poison - Chaffy Sachdeva; Kshema Thakur; Aditi Sharma; Krishan Kumar Sharma (Indian Journal of Clinical Biochemistry, 2018)

Insights into maize genome editing via CRISPR/Cas9 - Astha Agarwal; Pranjal Yadava; Krishan Kumar; Ishwar Singh; Tanushri Kaul; Arunava Pattanayak; Pawan Kumar Agrawal (Physiology and Molecular Biology of Plants, 2018)

Index-based assessment of suitability of water quality for irrigation purpose under Indian conditions - Surjeet Singh; N. C. Ghosh; Suman Gurjar; Gopal Krishan; Sumant Kumar; Preeti Berwal (Environmental Monitoring and Assessment, 2018)

Microbial taxonomy in the era of OMICS: application of DNA sequences, computational tools and techniques - Nitish Kumar Mahato; Vipin Gupta; Priya Singh; Rashmi Kumari; Helianthous Verma; Charu Tripathi; Pooja Rani; Anukriti Sharma; Nirjara Singhvi; Utkarsh Sood; Princy Hira; Puneet Kohli; et al. (Antonie van Leeuwenhoek, 2017)

Dynamic interaction of trace gases (VOCs, ozone, and NOx) in the rural atmosphere of sub-tropical India - Amit Kumar; Deepak Singh; Kumar Anandam; Krishan Kumar; Vinod Kumar Jain (Air Quality, Atmosphere & Health, 2017)

Implicating the potential role of orexin in hypertension - Monika Rani; Raghuvansh Kumar; Pawan Krishan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Lipid Nanocarrier-Mediated Drug Delivery System to Enhance the Oral Bioavailability of Rifabutin - Pradip Nirbhavane; Nalini Vemuri; Neeraj Kumar; Gopal Krishan Khuller (AAPS PharmSciTech, 2017)

Genetic structure of Pyrenophora teres f. teres and P. teres f. maculata populations from western Canada - Alireza Akhavan; T. Kelly Turkington; Berisso Kebede; Kequan Xi; Krishan Kumar; Andy Tekauz; H. Randy Kutcher; James R. Tucker; Stephen E. Strelkov (European Journal of Plant Pathology, 2016)

Spatial and temporal variability of VOCs and its source estimation during rush/non-rush hours in ambient air of Delhi, India - Deepak Singh; Amit Kumar; Bhupendra Pratap Singh; Kumar Anandam; Manoj Singh; Usha Mina; Krishan Kumar; Vinod Kumar Jain (Air Quality, Atmosphere & Health, 2016)

Evaluation of seasonal variations in abundance of BTXE hydrocarbons and their ozone forming potential in ambient urban atmosphere of Dehradun (India) - Neetu Bauri; Pradip Bauri; Krishan Kumar; V. K. Jain (Air Quality, Atmosphere & Health, 2016)

Spatial and temporal variability of surface ozone and nitrogen oxides in urban and rural ambient air of Delhi-NCR, India - Amit Kumar; Deepak Singh; Bhupendra Pratap Singh; Manoj Singh; Kumar Anandam; Krishan Kumar; V. K. Jain (Air Quality, Atmosphere & Health, 2015)

Genomic-derived microsatellite markers for diversity analysis in Jatropha curcas - Ramanuj Maurya; Astha Gupta; Sunil Kumar Singh; Krishan Mohan Rai; Chandrawati; Ratna Katiyar; Samir V. Sawant; Hemant Kumar Yadav (Trees, 2015)

Detection of antibodies to Toxoplasma gondii in domesticated ruminants by recombinant truncated SAG2 enzyme-linked immunosorbent assay - Harkirat Singh; Anup Kumar Tewari; Ashok Kumar Mishra; Biswaranjan Maharana; Vikrant Sudan; Opinder Krishan Raina; Jammi Raghavendra Rao (Tropical Animal Health and Production, 2015)

Analysis of temperature variability over north-west part of India for the period 1970–2000 - Monika Punia; Suman Nain; Amit Kumar; Bhupendra Pratap Singh; Amit Prakash; Krishan Kumar; V. K. Jain (Natural Hazards, 2015)

One-pot synthesis and cytotoxic evaluation of amide-linked 1,4-disubstituted 1,2,3-bistriazoles - Kashmiri Lal; C. P. Kaushik; Krishan Kumar; Ashwani Kumar; Asif Khurshid Qazi; Abid Hamid; Sundeep Jaglan (Medicinal Chemistry Research, 2014)

Assessment of indoor air concentrations of VOCs and their associated health risks in the library of Jawaharlal Nehru University, New Delhi - Amit Kumar; Bhupendra Pratap Singh; Monika Punia; Deepak Singh; Krishan Kumar; V. K. Jain (Environmental Science and Pollution Research, 2014)

An approach to develop a model for describing the influence of fluoride-contaminated irrigation water on physiological responses in poplar (Populus deltoides clone S7C15) - Munna Singh; Krishan Kumar Verma; Chhedi Lal Verma (Acta Physiologiae Plantarum, 2013)

Serum levels of angiogenic and anti-angiogenic factors: their prognostic relevance in locally advanced hepatocellular carcinoma - Bal Krishan Sharma; Radhika Srinivasan; Shweta Kapil; Bhupesh Singla; Nitin Saini; Yogesh Kumar Chawla; Anuradha Chakraborti; Ajay Duseja; Naveen Kalra; Radha Krishan Dhiman (Molecular and Cellular Biochemistry, 2013)

Angiogenic and anti-angiogenic factor gene transcript level quantitation by quantitative real time PCR in patients with hepatocellular carcinoma - Bal Krishan Sharma; Radhika Srinivasan; Shweta Kapil; Bhupesh Singla; Yogesh Kumar Chawla; Anuradha Chakraborti; Nitin Saini; Ajay Duseja; Ashim Das; Naveen Kalra; Radha Krishan Dhiman (Molecular Biology Reports, 2013)

Antimicrobial Activity and Identification of 4, 22-Stigmastadiene-3-one and Some Other Compounds in Motha Dhaman Grass Cenchrus setigerus from Tribal Area of Western Rajasthan - Premlata Singariya; Padma Kumar; Krishan Kumar Mourya (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Erratum to: Synthesis and biologic activities of some novel heterocyclic chalcone derivatives - Punita Sharma; Suresh Kumar; Furqan Ali; Sumati Anthal; Vivek K. Gupta; Inshad A. Khan; Surjeet Singh; Payare L. Sangwan; Krishan A. Suri; Bishan D. Gupta; Devinder K. Gupta; Prabhu Dutt; et al. (Medicinal Chemistry Research, 2013)

Synthesis and biologic activities of some novel heterocyclic chalcone derivatives - Punita Sharma; Suresh Kumar; Furquan Ali; Sumati Anthal; Vivek K. Gupta; Inshad A. Khan; Surjeet Singh; Payare L. Sangwan; Krishan A. Suri; Bishan D. Gupta; Devinder K. Gupta; Prabhu Dutt; et al. (Medicinal Chemistry Research, 2013)

Dichloroacetate reverses the hypoxic adaptation to bevacizumab and enhances its antitumor effects in mouse xenografts - Krishan Kumar; Simon Wigfield; Harriet E. Gee; Cecilia M. Devlin; Dean Singleton; Ji-Liang Li; Francesca Buffa; Melanie Huffman; Anthony L. Sinn; Jayne Silver; Helen Turley; Russell Leek; et al. (Journal of Molecular Medicine, 2013)

The effects of meteorological parameters in ambient noise modelling studies in Delhi - Deepak Singh; Amit Prakash; A. K. Srivastava; Krishan Kumar; V. K. Jain (Environmental Monitoring and Assessment, 2013)

Developing a mathematical model for variation of physiological responses of Jatropha curcas leaves depending on leaf positions under soil flooding - Krishan Kumar Verma; Munna Singh; Chhedi Lal Verma (Acta Physiologiae Plantarum, 2012)

Identification and mapping of two powdery mildew resistance genes in Triticum boeoticum L. - Parveen Chhuneja; Krishan Kumar; Daniel Stirnweis; Severine Hurni; Beat Keller; Harcharan S. Dhaliwal; Kuldeep Singh (Theoretical and Applied Genetics, 2012)

Anti-arthritic activity of agnuside mediated through the down-regulation of inflammatory mediators and cytokines - Anjali Pandey; Sarang Bani; Naresh Kumar Satti; Bishan Dutt Gupta; Krishan Avtar Suri (Inflammation Research, 2012)

Development and characterization of genomic and expressed SSRs for levant cotton (Gossypium herbaceum L.) - Satya Narayan Jena; Anukool Srivastava; Krishan Mohan Rai; Alok Ranjan; Sunil K. Singh; Tarannum Nisar; Meenal Srivastava; Sumit K. Bag; Shrikant Mantri; Mehar Hasan Asif; Hemant Kumar Yadav; Rakesh Tuli; et al. (Theoretical and Applied Genetics, 2012)

Genome-wide transcriptomic analysis of cotton under drought stress reveal significant down-regulation of genes and pathways involved in fibre elongation and up-regulation of defense responsive genes - Kethireddy Venkata Padmalatha; Gurusamy Dhandapani; Mogilicherla Kanakachari; Saravanan Kumar; Abhishek Dass; Deepak Prabhakar Patil; Vijayalakshmi Rajamani; Krishan Kumar; Ranjana Pathak; Bhupendra Rawat; Sadhu Leelavathi; Palakolanu Sudhakar Reddy; et al. (Plant Molecular Biology, 2012)

A Wavelet-based Neural Network Model to Predict Ambient Air Pollutants’ Concentration - Amit Prakash; Ujjwal Kumar; Krishan Kumar; V. K. Jain (Environmental Modeling & Assessment, 2011)

Chemoprotective Role of Triphala Against 1,2-Dimethylhydrazine Dihydrochloride Induced Carcinogenic Damage to Mouse Liver - Aditi Sharma; Krishan Kumar Sharma (Indian Journal of Clinical Biochemistry, 2011)

Decline of groundwater tables in the upper Yamuna basin: Causes and management strategies - Krishan Kumar; S. K. Gupta (Irrigation and Drainage, 2010)
Amongst the three drainage basins in Haryana (India), the upper Yamuna and upper Ghaggar basins are experiencing groundwater table declines in good quality aquifers. Rice–wheat crop rotation widely adopted in this region is blamed for this situation. A number of groundwater regime maps were prepared to assess long‐term groundwater table behaviour in these basins. The water levels during the past three decades (1974–2004) registered an annual decline varying from 30 to 60 cm. The analysis revealed that a saving of 15 cm of water in rice–wheat cropping would be able to halt the declining groundwater table. The rainfall data of Kurukshetra district for the period (1974–2004) revealed that most surface drainage surplus could be used as additional surface storage in rice fields and for groundwater recharge. Evapotranspiration calculated using the FAO CROPWAT model revealed that the evapotranspiration (ET) of the short duration crop is about 88% of the normal rice crop (transplanted on 20 June), although its duration from transplanting to maturity is almost half of the normal rice crop. Similarly, the ET of the crop transplanted one month in advance of the normal rice crop is 25–30% more. It is believed that these two aberrations aggravated the groundwater table situation more than the rice–wheat cropping itself. The review through a desk study identified a number of management strategies that could help to save 15 cm or even more water in the rice–wheat system. It is concluded that it should be possible to sustain groundwater irrigation even with rice–wheat cropping (without aberrations) at the current level in these parts of the basins. Copyright © 2009 John Wiley & Sons, Ltd.

Tannase production by Aspergillus fumigatus MA under solid-state fermentation - Manjit; Anita Yadav; N. K. Aggarwal; Krishan Kumar; Anil Kumar (World Journal of Microbiology and Biotechnology, 2008)

ATRA promotes alpha tocopherol succinate-induced apoptosis in freshly isolated leukemic cells from chronic myeloid leukemic patients - Surender Kumar; Krishan Lal Khanduja; Neelam Verma; Subhash C. Verma; Pramod Kumar Avti; Chander Mohan Pathak (Molecular and Cellular Biochemistry, 2007)

Genetic variability and association studies in pod and seed traits of Pongamia pinnata (L.) Pierre in Haryana, India - Naresh Kaushik; Sushil Kumar; Krishan Kumar; R. S. Beniwal; N. Kaushik; S. Roy (Genetic Resources and Crop Evolution, 2007)

Reactive oxygen species generation and mitochondrial dysfunction in the apoptotic cell death of human myeloid leukemia HL-60 cells by a dietary compound withaferin A with concomitant protection by N-acetyl cysteine - Fayaz Malik; Ajay Kumar; Shashi Bhushan; Sheema Khan; Aruna Bhatia; Krishan Avtar Suri; Ghulam Nabi Qazi; Jaswant Singh (Apoptosis, 2007)

Investigations on surface and subsurface drainage requirements at regional scale - Krishan Kumar; J. Singh; S. K. Gupta (Irrigation and Drainage, 2006)
Amongst the three drainage basins in Haryana (India), the inland drainage basin is most prone to surface stagnation, rise in groundwater table and soil salinization. In order to understand the surface and subsurface drainage requirements of this basin, a number of groundwater regime maps (groundwater table contour map, depth to groundwater table map, groundwater fluctuation map and groundwater quality map) were prepared to assess long‐term groundwater table behaviour in a part (comprising Rohtak and Jhajjar districts) of this basin for the period 1984–98. Groundwater movement was observed to occur towards the central part of the study area, a possible cause of waterlogging and degradation in groundwater quality. The groundwater levels during the past two and a half decades (1974–98) registered a rise varying from 1 to 19 m with an average rise of 21 cm yr −1 . The rainfall data of Rohtak and Jhajjar districts for the period (1975–98) were analysed for different frequencies of exceedance to determine 1, 2 and 3 days of consecutive rainfall. The surface drainable surplus was calculated taking into account the water storage in the soil profile, infiltration rates and evaporation that varied from 30–35, 35–40 and 5 mm day −1 respectively. The drainable surplus for consecutive 1, 2 and 3 days' rainfall for a 5‐year return period was 161, 113 and 0 m 3 s −1 respectively. The existing surface drainage system with a capacity of 170 m 3 s −1 and with availability of dead storage, could handle 1 and 2 days' consecutive rainfall for a 5‐year return period when full initial storage of 30–35 cm (equivalent to 50% of the available moisture) is available in the soil profile. From the groundwater regime maps, it was also estimated that nearly 16% of the study area (57 932 ha) required treatment with subsurface drainage. Therefore, a groundwater model (SWAP) was used to predict the subsurface drainable surplus considering various inputs related to the water balance of the area. The subsurface drainable surplus over the simulated years ranged between 0.4 and 1.92 mm day −1 . This range is quite close to the recommended range of the subsurface drainage coefficient for this region on the basis of field trials. The study of irrigation and drainage maps of the area revealed that there is a need to strengthen field surface drains and introduce subsurface drainage in the area. As such, the methodology proposed in this paper could be used to investigate drainage requirements on a regional scale. Copyright © 2006 John Wiley & Sons, Ltd.

Salt stress response in rice: genetics, molecular biology, and comparative genomics - Chandan Sahi; Amanjot Singh; Krishan Kumar; Eduardo Blumwald; Anil Grover (Functional & Integrative Genomics, 2006)

Rabi onion-intercropping in autumn planted sugarcane - Avtar Singh; Krishan Kumar Vashist (Sugar Tech, 2004)

Cardioprotection from ischemia and reperfusion injury by Withania somnifera: A hemodynamic, biochemical and histopathological assessment - Ipseeta Mohanty; Suresh Kumar Gupta; Keval Krishan Talwar; Amit Dinda; Sujata Joshi; Pankaj Bansal; Amit Saxena; Dharamvir Singh Arya (Molecular and Cellular Biochemistry, 2004)

Release of pro-inflammatory mediators during myocardial ischemia/reperfusion in coronary artery bypass graft surgery - Madhulika Sharma; Nirmal Kumar Ganguly; Gaurav Chaturvedi; Shyam K.S. Thingnam; Siddhartha Majumdar; Rajendar Krishan Suri (Molecular and Cellular Biochemistry, 2003)

A possible role of HSP 70 in mediating cardioprotection in patients undergoing CABG - Madhulika Sharma; Nirmal Kumar Ganguly; Gaurav Chaturvedi; Shyam K.S. Thingnam; Siddhartha Majumdar; Rajendar Krishan Suri (Molecular and Cellular Biochemistry, 2003)

Intercropping studies in spring planted sugarcane under flood plain conditions - Krishan Kumar Vashist; Hargopal Singh; Avtar Singh (Sugar Tech, 2003)